Increasing incidence of prostate cancer in Taiwan: A study of related factors using a nationwide health and welfare database. Issue 39 (25th September 2020) - Lin, Po-Hung; Chang, Su-Wei; Tsai, Ling-Hsuan; Kan, Hung-Cheng; Liu, Jui-Ming; Chuang, Cheng-Keng; Pang, See-Tong; Yu, Kai-Jie
Abstract : Abstract: Over the past decades, the incidence of prostate cancer in Taiwan kept rising. Many possible factors including the utility of prostate specific antigen tests, lifestyle remodeling, and patient's comorbidities may contribute to the increasing of incidence or prostate cancer. We aim to use the nationwide Health and Welfare Database (HWD) to investigate possible associated factors. We used HWD, a nationwide database of medical information, to assess the incidence of prostate cancer, utilization of prostate-specific antigen (PSA) test, and underlying diseases of patients and to evaluate whether there was a common trend among these factors. In total, 32, 508 patients with newly diagnosed prostate cancer from 2006 to 2013 were identified. The incidence rate of prostate cancer per 100, 000 men increased from 35.47 in 2006 to 52.87 in 2012. The number of patients with prostate cancer and underlying diseases related to metabolic syndrome increased every year. The number of total PSA tests and patients undergoing PSA testing, as well as average times of PSA testing per person in the whole population, increased every year. The average PSA test times of patients with newly diagnosed prostate cancer within 3 years before the diagnosis of prostate cancer also increased every year. There was a high correlation between the average PSA test times and the number of patients with newly diagnosed prostate cancer ( r 2  = 0.9734). The trends of incidence of prostate cancer, utilization of PSA testing, and underlying diseases related to metabolic syndrome at the diagnoses of cancer were similar, increasing every year in the study period. The results suggested that increasing use of PSA tests may increase the diagnosis of prostate cancers. Underlying diseases related to metabolic syndrome might also affect the incidence of prostate cancer.